MODEL DISCOVERY LEARNING: EFEKTIVITAS TERHADAP PEMAHAMAN KONSEP DAN KEMANDIRIAN BELAJAR SISWA - Nurul nur hidayah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Mathematics learning at the junior high school level continues to face challenges in improving students' conceptual understanding and learning independence, as reflected in their limited engagement in the learning process and tendency to receive information passively. This study aimed to describe the implementation of the discovery learning model and identify indications of its success in supporting students' mathematical conceptual understanding and learning independence at SMP Negeri 8 Pontianak. The research employed a quantitative approach using a pre-experimental one-shot case study design involving 32 seventh-grade students selected through simple random sampling. The research instruments included a conceptual understanding test, observation sheets for student activities and lesson implementation, student response questionnaires, and learning independence questionnaires. Data were analyzed descriptively using SPSS version 27. The findings revealed that students' conceptual understanding improved across successive measurements and reached good to very good categories. In addition, student activities, lesson implementation, student responses, and learning independence also demonstrated positive outcomes based on the predetermined criteria. These findings indicate that the implementation of the discovery learning model can foster a more active learning environment and support the enhancement of students' mathematical conceptual understanding and learning independence. Therefore, the discovery learning model has the potential to serve as an alternative instructional approach for improving the quality of mathematics learning at the junior high school level. ABSTRAK Pembelajaran matematika di tingkat SMP masih menghadapi tantangan dalam meningkatkan pemahaman konsep dan kemandirian belajar siswa, yang ditunjukkan oleh rendahnya keterlibatan siswa dalam proses pembelajaran dan kecenderungan menerima informasi secara pasif. Penelitian ini bertujuan untuk menggambarkan implementasi model discovery learning serta mengidentifikasi indikasi keberhasilannya dalam mendukung pemahaman konsep dan kemandirian belajar matematika siswa di SMP Negeri 8 Pontianak. Penelitian menggunakan pendekatan kuantitatif dengan desain pra-eksperimen one-shot case study yang melibatkan 32 siswa kelas VII yang dipilih melalui teknik simple random sampling. Instrumen penelitian terdiri atas tes pemahaman konsep, lembar observasi aktivitas siswa dan keterlaksanaan pembelajaran, angket respons siswa, serta angket kemandirian belajar. Data dianalisis secara deskriptif menggunakan bantuan SPSS versi 27. Hasil penelitian menunjukkan bahwa pemahaman konsep siswa mengalami peningkatan pada setiap pengukuran dan berada pada kategori baik hingga sangat baik. Selain itu, aktivitas siswa, keterlaksanaan pembelajaran, respons siswa, dan kemandirian belajar juga menunjukkan capaian positif sesuai kriteria yang ditetapkan. Temuan ini mengindikasikan bahwa penerapan model discovery learning mampu menciptakan pembelajaran yang lebih aktif serta mendukung penguatan pemahaman konsep dan kemandirian belajar matematika siswa. Dengan demikian, model discovery learning berpotensi menjadi alternatif pembelajaran yang relevan untuk meningkatkan kualitas proses belajar matematika di tingkat SMP.